2014
DOI: 10.5812/ircmj.10431
|View full text |Cite
|
Sign up to set email alerts
|

Rubella Immunity in Women of Childbearing Age, Eight Years After the Immunization Program in Iran

Abstract: Background:Rubella is a viral disease with a worldwide distribution. Mass vaccination campaigns have increased the vaccine coverage in the world with substantial impact on reduction of rubella infections. In Iran, the national measles-rubella campaign, targeting individuals 5-25 years old, was initiated in 2003 and mass childhood vaccination against measles, rubella and mumps has continued ever since.Objectives:The aim of this study was to evaluate the efficacy of routine vaccination on rubella immunity among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…12,19 While results of the Barari Sawadkohi et al study showed a contradict trend. 20 The rate of rubella immunity in migrants is relatively lower. Greenaway et al showed that immigrant women were more susceptible to rubella (Odds ratio = 1.7).…”
Section: Discussionmentioning
confidence: 99%
“…12,19 While results of the Barari Sawadkohi et al study showed a contradict trend. 20 The rate of rubella immunity in migrants is relatively lower. Greenaway et al showed that immigrant women were more susceptible to rubella (Odds ratio = 1.7).…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, until 2003, vaccination against rubella was not routinely performed and seroepidemiological studies revealed that 10% of susceptible women of reproductive age were exposed to rubella infection. Seroepidemiological assessment, following public vaccination against Measles-Rubella in 33 million 15 to 25 year-old people showed that more than 97% had gained immunity to rubella ( 9 - 12 ). Currently, rubella-measles-mumps vaccines are routinely administered together to 12 and 18 month-old children; however, because of changes in immunity level over time ( 13 - 15 ), it is necessary to conduct periodical assessment of immunity to rubella in susceptible age groups in various parts of the country to prevent CRS.…”
Section: Introductionmentioning
confidence: 99%